Optimizing spare part monitoring: Innovative dashboard system design for commanditaire vennotschaap using rapid application development - Lorensa Siallagan; Hanafi Hanafi (Journal of Computer-based Instructional Media, 2024)
This research focuses on digital transformation at the Try Jaya Mobil workshop, which relies on manual processes for recording spare parts sales transactions and generating financial reports. This manual process causes various challenges, such as mismatches between incoming data and orders and a lack of historical sales records that hinder data search and analysis. The absence of a computerized system also reduces stock management and customer service efficiency. This research uses the Rapid Application Development (RAD) method to design a more sophisticated spare parts monitoring information system. The Rapid Application Development approach enables iterative and rapid software development, involving users at every stage. The information system is designed to improve accuracy, speed, and operational efficiency and enable better stock recording and monitoring. The results show that implementing a RAD-based information system can significantly improve customer service and Try Jaya Mobil's competitiveness in the market. Evaluation of the system after implementation showed improvements in operational efficiency, data accuracy, and user satisfaction. With this digital transformation, Try Jaya Mobil is expected to optimize its services and strengthen its competitive automotive industry position.